Ending Modern-Day Slavery: A Research on China and Laos Anti-Human Trafficking Efforts - Oupady, Phansamai; Chen, Shixiang; Douansouvanh, Vilaikham; Kombate, Bienmali (Journal of Public Administration and Governance, 2022)
Human trafficking affects a surprisingly large number of adolescents around the globe, and thus, become a major issue in our decade requesting cooperation between countries to fight against it. To accompany this fight, researchers and scholars must also play the role of the investigator to identify the threats and convoy the smooth implementation of these activities. In this context, we aimed in this paper to assess the Laos-China bilateral anti-human trafficking cooperation (LC-BLIDC) against human trafficking between the two countries. The data was collected from a sample of 168 professionals who work to fight against human trafficking activities in Laos within the framework of LC-BLIDC. The study's empirical findings revealed that the attributes of individuals who have work experience in anti-human trafficking are associated with the success of the LC-BLIDC. The study, therefore, suggests training and education activities to be implemented with a focus on the individual instead of the department level.